Phylogenomics provides new insight into evolutionary relationships and genealogical discordance in the reef-building coral genus Acropora - Rosser, N.; Thomas, L.; Stankowski, S.; Richards, Zoe; Kennington, J.; Johnson, M. (The Royal Society Publishing, 2016)
Understanding the genetic basis of reproductive isolation is a long-standing goal of speciation research. In recently diverged populations, genealogical discordance may reveal genes and genomic regions that contribute to the speciation process. Previous work has shown that conspecific colonies of Acropora that spawn in different seasons (spring and autumn) are associated with highly diverged lineages of the phylogenetic marker PaxC. Here, we used 10 034 single-nucleotide polymorphisms to generate a genome-wide phylogeny and compared it with gene genealogies from the PaxC intron and the mtDNA Control Region in 20 species of Acropora, including three species with spring- and autumn-spawning cohorts. The PaxC phylogeny separated conspecific autumn and spring spawners into different genetic clusters in all three species; however, this pattern was not supported in two of the three species at the genome level, suggesting a selective connection between PaxC and reproductive timing in Acropora corals. This genome-wide phylogeny provides an improved foundation for resolving phylogenetic relationships in Acropora and, combined with PaxC, provides a fascinating platform for future research into regions of the genome that influence reproductive isolation and speciation in corals.